Transformasi Pemantauan Energi: Kontrol Daya Listrik 3 Fasa Dengan Antarmuka Grafis Pengguna (GUI) Secara Langsung - Wahyu Pratama, Erik; Kiswantono, Agus; Saidah (Fakultas Teknik Universitas Bhayangkara Surabaya, 2023)
Graphical user interface is a subset of HCI in the form of interaction between humans and machines through a graphical user interface. GUI is used by various fields of engineering, electronics, economics and even medicine. The development of graphic hardware has triggered various fields to visualize various models in order to increase knowledge. This systematic review aims to provide clear information about the influence of the graphical user interface on monitoring voltage, current, and frequency. Testing the ESP32 microcontroller that has been carried out shows that the output voltage at condition 1 averages a value of 3.5 V and when at condition 0, the output voltage is 0.38 V. Designing a 3-phase electricity monitoring system equipped with a power controller using a desktop application in real time, this is made for efficient use of electricity and control in electrical safety systems in an industry